2019
DOI: 10.1108/imds-05-2019-0264
|View full text |Cite
|
Sign up to set email alerts
|

A model-driven decision approach to collaborative planning and obsolescence for manufacturing operations

Abstract: Purpose The purpose of this paper is to present the model-driven decision support system (DSS) for small and medium manufacturing enterprises (SMMEs) that actively participates in collaborative activities and manages the planned obsolescence in production. In dealing with the complexity of such demand and supply scenario, the optimisation models are also developed to evaluate the performance of operations practices. Design/methodology/approach The model-driven DSS for SMMEs, which uses the optimisation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In general, this framework is more comprehensive and can lead to better success. Other literature (Kuik and Diong, 2019;Nakano, 2009) discussed steps to execute collaborative planning. Researchers (Gupta and Andersen, 2018;Liu et al, 2020;Nyaga et al, 2010) also demonstrated how to measure collaboration performance/intensity based on the elements described above.…”
Section: Collaboration Executionmentioning
confidence: 99%
“…In general, this framework is more comprehensive and can lead to better success. Other literature (Kuik and Diong, 2019;Nakano, 2009) discussed steps to execute collaborative planning. Researchers (Gupta and Andersen, 2018;Liu et al, 2020;Nyaga et al, 2010) also demonstrated how to measure collaboration performance/intensity based on the elements described above.…”
Section: Collaboration Executionmentioning
confidence: 99%
“…In this study, the system architecture of a model driven DSS is divided into the hardware infrastructure and software application packages. The system design is adopted from Kuik and Diong (2019). Basically, there are three architecture modules in the system.…”
Section: System Architecturementioning
confidence: 99%
“…For implementation, the four-phase decision making model as adopted from Kuik and Diong (2019) is applied. The decision model has four phases including intelligence, design and choice and implementation phases.…”
Section: System Architecturementioning
confidence: 99%
“…It was hard to find a suitable partnership to develop a nonhierarchical network, but Industry 4.0 tools seem to support the CMM structure [19]. A network needs to be organized that integrates the various customer-supplier and design-support aspects most effectively in order to increase the efficiency of the business and production [20].…”
Section: Requirements Of Vertical Integrationmentioning
confidence: 99%